Effects and coping mechanisms associated with Premenstrual Syndrome among female University Students in Central Uganda: A Cross-sectional Study - Atim, Elizabeth; Nabushawo Okecho, Florence; Ndagire, Regina; Lwanira Nassozi, Catherine (Student’s Journal of Health Research Africa, 2022)
Background The cyclic nature of Premenstrual Syndrome (PMS) affects those with severe symptoms in ways that make them incapacitated or inefficient every month impairing their quality of life. This problem in Uganda is compounded by the cultural stigma associated with menstruation making it difficult for ladies and communities to address the associated problems. Therefore, this study sought to identify how Premenstrual Syndrome affects the quality of life of female University students in Central Uganda in terms of effects and coping mechanisms. Methodology A cross-sectional study was carried out using a questionnaire between November 2021 and May 2022. 238 participants from 4 universities who met the inclusion criteria were given self-administered questionnaires on PMS symptoms, effects and coping mechanisms. The data was analysed to obtain frequencies and percentages. Statistically significant associations between PMS and Effects of PMS as well as the Coping mechanism were determined using Chi-square correlations. Results At least 70 (33%) of the 212 respondents reported that the PMS symptoms affected either their school and/or their relationships or their daily activities plus home chores. Statistically significant effects of PMS on school efficiency were: sleeping in class χ2(1, n=212) = 4.957, p=0.026; and being late on assignments χ2(1, n=212) = 6.279, p=0.012. Coping mechanisms that were found to be statistically significantly associated with PMS at α-level of 5% were: hiding or locking self in a room χ2(1, n=212) = 4.846, p=0.028; taking alcohol χ2(1, n=212) = 5.115, p=0.024; seeing a health worker χ2(4, n=212) = 14.201, p=0.007; and taking pain killers χ2(1, n=212) = 5.202, p=0.03. Conclusion PMS was significantly affecting school efficiency of students. Recommendation There are still huge knowledge gaps about PMS that need addressing. Some students reported that they used herbal preparations for PMS symptoms which need to be investigated for potential pharmaceutical development.